Ibsen’s Pharmakon: Socrates and Stockmann - Tomljenović, Ana (Poznańskie Studia Slawistyczne, 2019)
Although An Enemy of the People has always been one of Ibsen’s most popular plays, ibsenology often dismisses it as a revolutionary pamphlet and the critique of the tyranny of the compact majority and the mediocrity of parliamentary democracy. Instead of focusing on the conflict that arises between the Conservatives and the Liberals, minority and majority, I want to draw attention to Ibsen’s poetic revolt. Building on Derrida’s study of the pharmakon in the Phaedrus, I argue that Ibsen continues to investigate the conflict between the speaker and the listener, between the actor and the audience, between speech and writing.